2010
DOI: 10.1016/j.resuscitation.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of residual leaning force on intrathoracic pressure during mechanical ventilation in children

Abstract: Aim Determine the effect of residual leaning force on intrathoracic pressure (ITP) in healthy children receiving mechanical ventilation. We hypothesized that application of significant residual leaning force (2.5 kg or 20% of subject body weight) would be associated with a clinically important change in ITP. Methods IRB-approved pilot study of healthy, anesthetized, paralyzed mechanically ventilated children (6 months to 7 years). Peak endotracheal pressure (ETP), a surrogate of ITP, was continuously measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…46 Although data are sparse regarding outcomes related to leaning, animal studies have shown that leaning increases right atrial pressure and decreases cerebral and coronary perfusion pressure, cardiac index, and left ventricular myocardial flow. [46][47][48] Human studies show that a majority of rescuers often lean during CPR and do not allow the chest to recoil fully. 49,50 Therefore, the expert panel agrees that leaning should be minimized.…”
Section: Full Chest Recoil: No Residual Leaningmentioning
confidence: 99%
“…46 Although data are sparse regarding outcomes related to leaning, animal studies have shown that leaning increases right atrial pressure and decreases cerebral and coronary perfusion pressure, cardiac index, and left ventricular myocardial flow. [46][47][48] Human studies show that a majority of rescuers often lean during CPR and do not allow the chest to recoil fully. 49,50 Therefore, the expert panel agrees that leaning should be minimized.…”
Section: Full Chest Recoil: No Residual Leaningmentioning
confidence: 99%
“…Two human studies have implicated incomplete chest wall recoil as negatively impacting hemodynamics, but were not performed on cardiac arrest patients. 37,38 Observational studies describe a lack of complete chest wall recoil, also referred to as leaning, during resuscitation from both OHCA and in-hospital cardiac arrest. 6,17,29,30 To our knowledge, there are no clinical data demonstrating an association between complete chest recoil and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete chest release during CPR has been observed to generate increased intrathoracic pressures during the chest release phase, consequently limiting the return of venous blood to the heart and reducing coronary and cerebral perfusion pressures 15 27–29. While incomplete release during CPR in older paediatric subjects has been observed in 25–50% of chest compressions,22 30 >97% of chest compressions achieved target release forces during CPR in adults 19.…”
Section: Discussionmentioning
confidence: 99%
“…Chest compression depth and compression rate targets were based on ERC and UKRC guideline recommendations: targeting depths of ‘at least one-third’ the external anterior–posterior (AP) chest diameter (≥36.7 mm for this manikin model) and a rate between 100 and 120 compressions/min 6 7. A chest release force target of <2.5 kg was defined to represent the residual chest compression force associated with a clinically significant increase in intrathoracic pressure in infants 15. Finally, a duty cycle target of 30–50% was defined to represent the most effective duty cycle range observed in infant animal surrogates 16–18.…”
Section: Methodsmentioning
confidence: 99%